A comprehensive analysis on the longitudinal fracture in the tool joints of drill pipes. (September 2017) - Wang, Xinhu; Li, Fangpo; Liu, Yonggang; Feng, Yaorong; Zhu, Lijuan
Abstract: The Longitudinal fractures or splits in tool joint box of drill pipe often occur, because the numbers of deep, directional, extended and horizontal oil wells are increasing. The mechanism of frictional heat check cracking of drill pipe tool joints was discussed in the standard API RP 7G. However, authors have identified that heat check cracking was just one of the cracking initiation mechanism, not crack propagation mechanism. This paper has reviewed 21 cases of this kind of failure analyzed by authors from year 2000 to 2015. Fracture surfaces and mechanical properties have been examined in this paper. It was found that there were various other causes of crack initiation, in addition to frictional heat check cracking, such as tong tooth bite marks and friction damage in internal threads. Such cracks propagated mostly via stress corrosion cracking (SCC) mechanism, although two cases was brittle cracking due to poor material toughness. The stress corrosion mechanism was related to hydrogen sulfide (H2 S) or ionic sulfur (S 2 − ), which came from the degradation of applied thread greases or drilling fluid ingredients. Although heat check cracks and tooth bite marks as crack initiation are common-place, the failure can be prevented through prevention of crack propagation. Failure data showed that although improved transverse material absorbed energy avoided longitudinal brittle cracking of the tool joint, stress corrosion cracking still occurred. The statistical analysis results showed that material hardness was related to the longitudinal cracking of drill pipe tool joints. It was demonstrated that if material hardness was restricted to less than HB310, the crack did not propagate. It was suggested that the material hardness of tool joints box should be revised to HB285–HB310, in addition that the transverse material Charpy absorbed energy of the tool joint should be specified. Highlights: Heat checking was not fracture cause of drill pipe tool joints as shown in API RP 7G. Heat check cracks, tong bite marks and friction damaged thread tooth were just cracking initiation. The mechanism of cracks propagation was mainly stress corrosion crack. Maximum material hardness of the tool joints should be HB310 in the API SPEC 5DP.